Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan Sekolah di MTS Raushan Fikri Islamic School - Hamidah D; Julkifli; Dewi Rulia Sitepu; Mardiati (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this research is to increase the awareness of school principals and teachers and other school members towards a democratic and cooperative working system, as well as increase assistance to assist, increase the ambition of teachers to improve the quality of their services to the maximum in their professional fields (expertise), and develop a sense of oneness and unity between leaders and teachers. This type of research includes field research or qualitative methods. The research subjects used in this study were the principal and all teachers at MTs Raushan Fikri Islamic School. The instrument used by the researcher, in this case is the main instrument and the supporting instrument. while the main instrument is the human itself, the supporting instruments are the observation guide and interview guide. The data analysis technique used in this research is the descriptive technique which includes three procedures, namely: Data Reduction, Data Presentation, Conclusion Drawing/Verification. The results in this study are the leadership of the principal plays a strong role in the formation of the human qualities he leads to becoming the nation's next generation. The obstacle was found in the form of frequent changes to the curriculum, so the plans or programs that had been made had to be changed based on the current curriculum. The principal's effort in improving the quality of education at MTs Raushan Fikri Langkat is by holding a meeting or meeting with students and parents to jointly explain their educational program and presentation so that the response can support the success of quality improvement at MTs Raushan Fikri Islamic School Langkat this can be implemented and realized.